Beyond Gesture: An Investigation into a Corporeal Language of Feminist Performative Anti-Painting - McCartney, Lauren (Curtin University, 2017)
This PhD explores how the female body can parody histories of objectification, and conventions of appropriate female behaviour. It examines how the performing female body has overcome masculine ideals of action painting, and applies a reading of anti-painting to the performative processes attributed to becoming painting, rather than a perceived final stage of being painting. It establishes forms of feminist performative painting that not only provoke patriarchal hierarchies in painting, but also reveal a corporeal feminism that defies them.